Post-implementation Review of the Himalaya Home Care Project for Home Isolated COVID-19 Patients in Nepal - Amatya, Rakchya; Mishra, Kritika; Karki, Kshitij; Puri, Isha; Gautam, Archita; Thapa, Sweta; Katwal, Urmila; Veer, Siddhesh; Zervos, John; Kaljee, Linda; Prentiss, Tyler; Zenlea, Kate; et al. (Frontiers in Public Health, 2022)
The emergence of coronavirus disease 2019 (COVID-19) has resulted in a pandemic that has significantly impacted healthcare systems at a global level. Health care facilities in Nepal, as in other low- and middle-income countries, have limited resources for the treatment and management of COVID-19 patients. Only critical cases are admitted to the hospital resulting in most patients in home isolation. Himalaya Home Care (HHC) was initiated to monitor and provide counseling to home isolated COVID-19 patients for disease prevention, control, and treatment. Counselors included one physician and four nurses. Data from 5823 and 3988 patients were entered in initial and follow-up forms on a REDCap database. The HHC counselors consulted on symptom management and information on home isolation during initial calls. The majority of patients who received counseling were satisfied. At follow-up, 98.4% of respondents reported that HHC prevented hospitalization, 76.5% reported they were able to manage their symptoms at home, and 69.5% reported that counseling helped to limit the spread of COVID-19 in their household. Telehealth can be an essential strategy for providing services while keeping patients and health providers safe during the COVID-19 pandemic.